Neutrinos and other matters : Selected works of Frederick Reines - Kropp, W; Moe, M; Price, L; Schultz, J; Sobel, H (Singapore World Scientific, 1991)
This volume is a collection of the scientific papers of Frederick Reines. The selected papers here cover many aspects of his work in neutrino physics, astrophysics and conservation law tests.
Includes bibliographical references
Keywords: Cơ bản